Measuring Operational Risk on according to International Requirements: An Applied Research in Bank of Baghdad- Private Shareholders Organization (Journal of Accounting and Financial Studies ( JAFS ), 2020)
This research aims to study and evaluate the reality of the Iraqi banks in terms of how they cope with the risks of the banking business, specifically banking operational risks, and to develop a model integrated to define, identify, measure and mitigate the impact of these risks on according to the Basel Committee requirements II about the dangers of Alchgal.uchir major search to the presence of weak results in the Iraqi banks in understanding and defining and measuring operational risks and not hedged properly, which avoids those banks operating losses as well as the results show there is a shortage in the equation of capital adequacy applied by the Iraqi banks because of non-observance of the minimum capital required to counter the risk calculation calculation operating according to the requirements and guidelines of the Basel Committee II.T he researcher found also within results to the fact that the lack of an appropriate approach is supported regulators overseeing the control of the performance of banks to identify and quantify operational risk , it reflected a weakness supervisory and oversight role played by the Central Bank of Iraq in the field of supervision and guidance on the performance of Iraqi banks in terms of hedged risk banking operation.